2013
DOI: 10.1166/jnn.2013.6951
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cellular RNA Nano-Particle Assembly by Splicing Factor SRp20

Abstract: Cellular RNA nano-particles (RNA granules) such as stress granule (SG) and P-body (PB) are translationally silenced mRNA-protein complexes. Previously, a genome-wide loss-of-function screen using oligomeric siRNAs targeting potential drug target genes was performed to identify genes that are involved in SG and PB assembly. SRp20 (SRSF3), a splicing regulator, was identified as a potential regulator for the RNA granule assembly. Here, we show that SRp20 is a bona-fide RNA granule component using antibody agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…We found that PA-induced stress led to neddylation of SRSF3 and degradation. A previous study investigating the formation of stress granules in U2OS cells reported that the neddylation enzyme UBE2M was essential for granule formation in response to arsenite, and furthermore showed through proteomic profiling that SRSF3 was neddylated on lysine 85 to promote stress granule assembly, as they had previously reported (25,55). Our results showed that SRSF3 is neddylated on lysine 11 under PA-induced oxidative stress but this modification targeted SRSF3 for degradation.…”
Section: Discussionsupporting
confidence: 76%
“…We found that PA-induced stress led to neddylation of SRSF3 and degradation. A previous study investigating the formation of stress granules in U2OS cells reported that the neddylation enzyme UBE2M was essential for granule formation in response to arsenite, and furthermore showed through proteomic profiling that SRSF3 was neddylated on lysine 85 to promote stress granule assembly, as they had previously reported (25,55). Our results showed that SRSF3 is neddylated on lysine 11 under PA-induced oxidative stress but this modification targeted SRSF3 for degradation.…”
Section: Discussionsupporting
confidence: 76%
“…13 SR proteins such as SRSF1 and SRSF3 shuttle between the nucleus and the cytoplasm and migrate into RNA granules, such as PBs and stress granules (SGs), where translationally silenced mRNAs and regulatory proteins are deposited. [24][25][26] These RNA granules harbor both mRNAs that have disassembled from translationally active polysomes and proteins including a eukaryotic translation initiation factor 4E (eIF4E), XRN1 (5 0 -3 0 exonuclease), FAST (Fas-activated serine/threonine kinase), TTP (tristetraprolin), and, notably, Argonaute, a key component of RISC (RNA-induced silencing complex), a complex involved in miRNA-mediated translational repression. 27,28 We show that SRSF3 and PDCD4 mRNA are colocalized to PBs.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, SR proteins have been investigated for their function in splicing (Lopato et al, 1999a(Lopato et al, , 1999b. In animal systems, SR proteins, apart from their role in pre-mRNA splicing, function in diverse processes associated with RNA metabolism and gene regulation, including mRNA export, stability and translation, chromatin binding, transcription elongation, subcellular localization of transcripts, genome stability and formation of cellular RNA granules, and miRNA processing structures (stress granules and processing bodies) (Long and Caceres, 2009;Shepard and Hertel, 2009;Risso et al, 2012;Yoon et al, 2013). Whether plant SR proteins, like their animal counterparts, have wide-ranging roles in other aspects of RNA metabolism remains to be seen.…”
Section: Trans-acting Factorsmentioning
confidence: 99%